Measuring Jobs-Linked Externalities in Private Investment Projects : A Fragility, Conflict, and Violence Perspective - Ricaldi, Federica (World Bank, Washington, DC, 2020)
This paper presents the rationale, the methodology and the results of the application of an innovative social rate of return (SRR) methodology in the context of an investment project (Gaza Solar Power project) financed through the Finance for Jobs (F4J) Series of Projects (SOP) in West Bank and Gaza. A key assumption behind this work is that creating jobs through private sector investment generates benefits above the market returns to the factors of production (capital, labor, and land). Moreover, in instances where the market returns would not be sufficient for the investment to take place because of elevated risks and market failures, these benefits constitute additional social returns that can justify and merit public financing support to enable fundamentally sound commercial investment to proceed and the benefits to be generated. The paper presents the methodology applied through the use of discrete choice experiment (DCE) in a cost-benefit analysis to better approximate a measurable social value to the benefits (jobs-linked externalities) generated by the investment project in Gaza.